2016
DOI: 10.1002/reg2.52
|View full text |Cite
|
Sign up to set email alerts
|

Planarian brain regeneration as a model system for developmental neurotoxicology

Abstract: Freshwater planarians, famous for their regenerative prowess, have long been recognized as a valuable in vivo animal model to study the effects of chemical exposure. In this review, we summarize the current techniques and tools used in the literature to assess toxicity in the planarian system. We focus on the planarian's particular amenability for neurotoxicology and neuroregeneration studies, owing to the planarian's unique ability to regenerate a centralized nervous system. Zooming in from the organismal to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 81 publications
(187 reference statements)
1
68
0
Order By: Relevance
“…As the peripheral site may play a role in aspects of OP toxicity (Kousba et al 2004), the differences in the DjChE peripheral site, as compared to mammalian AChE, provides an opportunity to distinguish between these effects. The unique regenerative capabilities of planarians allows one not only to compare toxicity on adult and developing animals in parallel (Hagstrom et al 2016), but also bears the potential to delineate how OP-induced neurological damage could be repaired.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the peripheral site may play a role in aspects of OP toxicity (Kousba et al 2004), the differences in the DjChE peripheral site, as compared to mammalian AChE, provides an opportunity to distinguish between these effects. The unique regenerative capabilities of planarians allows one not only to compare toxicity on adult and developing animals in parallel (Hagstrom et al 2016), but also bears the potential to delineate how OP-induced neurological damage could be repaired.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that the freshwater planarian Dugesia japonica is a valuable in vivo model for neurotoxicity studies (Hagstrom et al 2015; Hagstrom et al 2016). The planarian’s capacity to regenerate after asexual reproduction or amputation - due to its large population of stem cells - make it well suited to study perturbations in neurodevelopment (Hagstrom et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Planarians have also been the subject of recent work in toxicology, as well as behavioral, ecological, and evolutionary biology research (Alvarez-Presas et al, 2008; Hagstrom et al, 2016, 2015; Hicks et al, 2006; Inoue et al, 2015; Levin et al, 2016; Lombardo et al, 2011; Majdi et al, 2014; Shomrat and Levin, 2013), broadening their use as a model beyond fields related to developmental biology. In the classroom, these charismatic organisms have been an important component in K-12 science education and tools are being developed to modernize their use in college level courses (Accorsi et al, 2017; Eberhardt et al, 2015; Pagan et al, 2009; Valverde, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The freshwater planarian Dugesia japonica has recently emerged as a valuable in vivo model for neurotoxicity studies, with particular focus on neurodevelopment (Hagstrom et al 2015; Hagstrom et al 2016). This asexual species naturally reproduces through transverse fission.…”
Section: Introductionmentioning
confidence: 99%